Cluster model calculations on Li6. - Ram, Valluri Sree. (University of Ottawa (Canada), 1970)
The radiative transition probabilities from the 3+ state at 2.18 Mev and the 0+ state at 3.56 Mev to the 1+ ground state are calculated using cluster model wave functions. In this model, the 3+ and the 1+ states are assumed to have an alpha-deuteron cluster structure and the 0+ state an alpha-deuteron cluster structure in which the deuteron cluster is excited to the lowest T = 1, S = 0 state. The results obtained were in reasonable agreement with the experimental values, thus confirming a good degree of accuracy of the cluster model wave functions for Li6.
Keywords: Physics, Theory.